2018
DOI: 10.3390/technologies6010022
|View full text |Cite
|
Sign up to set email alerts
|

Remote Care Technology: A Systematic Review of Reviews and Meta-Analyses

Abstract: Objectives-To identify the technologies that are being used in the remote care of patients with chronic conditions, and their most relevant outcomes. Methods-A systematic review of reviews and meta-analyses. Results-Fifty-one systematic reviews and meta-analyses related to diabetes, congestive heart failure, chronic obstructive pulmonary disease, mental and behavioral diseases, cancer, hypertension, asthma, multiple sclerosis, chronic renal disease, and obesity were retrieved; these studies compared the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 60 publications
0
24
0
Order By: Relevance
“…In the remaining 8 reviews [2], [5], [11], [18], [34], [35], [50] and [51] discussed interventions were partially integrated into traditional healthcare systems and highlighted challenges which hampered complete integration into clinical work ows. For example, one review [34] identi ed two key barriers to integration: the 'diversity of available technologies' and 'lack of comprehensive guiding framework for standardizing data collection and integration'.…”
Section: Levels Of Integration Within Traditional Healthcare Systems mentioning
confidence: 99%
See 2 more Smart Citations
“…In the remaining 8 reviews [2], [5], [11], [18], [34], [35], [50] and [51] discussed interventions were partially integrated into traditional healthcare systems and highlighted challenges which hampered complete integration into clinical work ows. For example, one review [34] identi ed two key barriers to integration: the 'diversity of available technologies' and 'lack of comprehensive guiding framework for standardizing data collection and integration'.…”
Section: Levels Of Integration Within Traditional Healthcare Systems mentioning
confidence: 99%
“…One of the above reviews [5] indicated that healthcare practitioners view some effects of mHealth on aspects such as their credibility and autonomy as impacting their acceptance of such tools and systems; while another [35] highlighted the lack of integration of community-based HIS in formal HMIS (without complete integration, there are duplicative efforts in data collection, analysis, and reporting), and the lack of technical capacity of community workers. Finally, review [51] observed that despite the huge research effort on remote care technology, there has not been a su cient number of successful interventions which have gone past the research environment and broadly taken up and routinely used in clinical settings.…”
Section: Levels Of Integration Within Traditional Healthcare Systems mentioning
confidence: 99%
See 1 more Smart Citation
“…These studies reported on smart city applications to support population surveillance, active ageing, healthy lifestyles, disabled people, response to emergencies, care services organization, and socialization. Conclusions: Most of the included articles were either of a descriptive and conceptual nature or in an early stage of development, which means that a major barrier for their dissemination is their lack of concreteness.Technologies 2019, 7, 58 2 of 16 mindedness; and smart living-quality of life of the individuals, namely health conditions, cultural and education facilities, housing quality, and touristic attractiveness.Although there is a significant number of systematic reviews related to healthcare provision supported by IT (e.g.,[6][7][8][9][10]), to the best of the authors' knowledge, systematic reviews of the literature related to the implementation of smart cities are scarce and address specific aspects (e.g., [11][12][13]). Since systematic evidence is required to inform smart city stakeholders and researchers about state of the art solutions, the systematic review reported by the present article aimed to identify the most relevant applications supported by smart city infrastructure with an impact in the provision of healthcare, which is a relevant component of smart living.…”
mentioning
confidence: 99%
“…Although there is a significant number of systematic reviews related to healthcare provision supported by IT (e.g.,[6][7][8][9][10]), to the best of the authors' knowledge, systematic reviews of the literature related to the implementation of smart cities are scarce and address specific aspects (e.g., [11][12][13]). Since systematic evidence is required to inform smart city stakeholders and researchers about state of the art solutions, the systematic review reported by the present article aimed to identify the most relevant applications supported by smart city infrastructure with an impact in the provision of healthcare, which is a relevant component of smart living.…”
mentioning
confidence: 99%